2009
DOI: 10.1111/j.1749-6632.2009.03946.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of LGR7 in the Primate Corpus Luteum Implicates the Corpus Luteum as a Relaxin Target Organ

Abstract: In women, the corpus luteum is the source of circulating relaxin. No previous studies have addressed whether the corpus luteum is also a relaxin target organ. We determined relaxin receptor LGR7 mRNA expression in human term pregnancy corpora lutea and non-human primate corpora lutea obtained during the menstrual cycle. Real-time RT-PCR demonstrated the expression of LGR 7 mRNA in both human and rhesus monkey corpora lutea. Rhesus monkey corpora lutea were obtained from naturally cycling animals following docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, we analyzed the presence of relaxin and its receptors at the protein levels in both oocytes and embryos. Ovarian follicular and corpora lutea cells were used as positive controls as already reported in previous studies [ 11 , 15 , 16 , 25 , 34 - 36 ]. Here, we used anti-human relaxin and RXFP1/2, whose antigenic regions were found to be highly similar among various mammalians (cattle, chimpanzee, dog, horse, human, and mice).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we analyzed the presence of relaxin and its receptors at the protein levels in both oocytes and embryos. Ovarian follicular and corpora lutea cells were used as positive controls as already reported in previous studies [ 11 , 15 , 16 , 25 , 34 - 36 ]. Here, we used anti-human relaxin and RXFP1/2, whose antigenic regions were found to be highly similar among various mammalians (cattle, chimpanzee, dog, horse, human, and mice).…”
Section: Discussionmentioning
confidence: 99%
“…38 Relaxin is also produced by the theca interna cells of follicles, 39 which are likely to be the primary contributors of the relaxin detected in follicular fluid. 40 RXFP1 messenger RNA (mRNA) has been detected in the corpus luteum of humans and monkeys 41 and specifically on granulosa and cumulus cells of pig antral follicles 42 and potentially in human granulosa cells of primordial, primary, and secondary follicles. 43 A variety of studies have suggested that circulating relaxin reaches its peak in the latter half of the luteal phase of the menstrual cycle with levels either low or nondetectable in other cycle stages.…”
Section: Expression Of Relaxin and Relaxin Receptors (Rxfp1) During The Menstrual Cyclementioning
confidence: 99%
“…Thus, steroid/P control of steroidogenic genes may be limited in the CL of SEP. There is evidence for regulation of primate luteal function by non-steroidal targets of CG such as prostaglandins (Bogan et al, 2008a), luteal relaxin production (Maseelall et al, 2009) and modulation of luteal cytokines (Townson and Liptak, 2003). All of these local factors were altered by CG, as noted in our previous microarray analysis (Bishop et al, 2011b), and may regulate more probesets than steroids alone.…”
Section: Discussionmentioning
confidence: 99%